Population and genetic structure of two dioecious timber species Virola surinamensis and Virola koschnyi (Myristicaceae) in southwestern Costa Rica - Riba Hernández, José Pablo (2014)
Selective logging regulations generally fail to account for sex ratios, sex size distribution, spatial patterns and genetic structure in dioecious timber species. Furthermore, sympatric congeneric dioecious tropical species are harvested under the same vernacular name, failing to account for potential variation in species population traits. This practice is expected to have deleterious consequences in the population density and reproduction of the least abundant species. Here we document density, sex ratios, sex size distribution, spatial patterns and genetic structure in two dioecious timber tree species, Virola surinamensis and V. koschnyi in southwestern Costa Rica. In addition, we assessed the probability that harvesting these two species under the same vernacular name will cause a significant decline in either sex density of the least abundant species, which is expected to unbalance sex ratios, therefore, reducing the reproductive potential of the species. In a 62 ha plot we tagged, geo-referenced and sampled for cambium tissue all adults of the two species (dbh > 30 cm) for genetic analyses. Microsatellites loci were used to describe genetic diversity parameters and spatial genetic structure. In a nuclear subplot (42 ha) we measured dbh and monitored sex expression during two reproductive events to describe population density, sex ratios, sex size distribution and spatial patterns. Adult density was twofold higher for V. surinamensis than V. koschnyi. The proportion of flowering males and females and diametric size distribution did not differ within species. Adults of both Virola species were spatially aggregated, but sexes were distributed randomly. We found a significant but weak spatial genetic structure for V. surinamensis, but not for V. koschnyi. Finally, there is a high probability (Multivariate hypergeometric distribution, p = 0.47) that harvesting these two species under the same vernacular name will cause a drastic decline in the density of male or female trees of V. koschnyi. Overall our results suggest that dioecy does not influence tree size or spatial distribution of these two timber species. The weak spatial genetic structure in V. surinamensis is likely due to clumped seed dispersal and absence of thinning during the recruitment of genetically related seeds to the adult stage. Harvesting these two species under the same vernacular name will have important consequences in the reproduction of V. koschnyi. We suggest that selective logging regulations for dioecious species should encourage appropriated species identification, ascertain the sex of reproductive individuals, harvest these species in proportion to their sex ratios and reduce the proportion of harvested individuals in the population.